Zoological vs. botanical nomenclature: a forgotten BioCode experiment from the times of the Strickland Code - Minelli, Alessandro (Zootaxa, 2008)
A code intended to apply to both zoological and botanical nomenclature was drafted in 1842–43 by a commission appointed by the fourth Congress of Italian Scientists on request of the zoologist Carlo Luciano Bonaparte, as a reaction to the recently published Strickland Code (1842). Large excerpts from the latter document and an English translation of documents related to the Italian initiative are presented in appendices.